(untitled) (Medico Legal Update, 2020)
It has long been believed that cytokines have an important function in immunopathology during viral infection. Coronavirus disease 2019 (Covid-19) is a contagious viral disease caused by severe acute respiratory syndrome coronavirus 2. Covid-19 can be fatal because of an overactive immune response and release of cytokines. This review focuses on the role of cytokines in COVID-19.